Potential Role of Phytochemicals Against Matrix Metalloproteinase Induced Breast Cancer; An Explanatory Review - Khan, Yusra Habib; Uttra, Ambreen Malik; Qasim, Sumera; Mallhi, Tauqeer Hussain; Alotaibi, Nasser Hadal; Rasheed, Maria; Alzarea, Abdulaziz Ibrahim; Iqbal, Muhammad Shahid; Alruwaili, Nabil Khulaif; Khan, Salah-Ud-Din; Alanazi, Abdullah Salah (Frontiers in Chemistry, 2021)
World Health Organization (WHO) estimated breast cancer as one of the most prevailed malignancy around the globe. Its incident cases are gradually increasing every year, resulting in considerable healthcare burden. The heterogeneity of breast cancer accounts for its differential molecular subtyping, interaction between pathways, DNA damaging and chronic inflammation. Matrix metalloproteinases (MMPs) are a group of zinc-containing, calcium dependent endopeptidases which play a substantial role in breast carcinogenesis through several mechanisms. These mechanisms include remodeling of extracellular matrix (ECM), cell proliferation and angiogenesis which promote metastasis and result in tumor progression. In this context, compounds bearing MMP inhibitory potential can serve as potent therapeutic agents in combating MMPs provoked breast cancer. Current systematic review aimed to encompass the details of potent natural lead molecules that can deter MMPs-provoked breast cancer. Following the critical appraisal of literature, a total of n=44 studies that explored inhibitory effect of phytochemicals on MMPs were included in this review. These phytoconstituents include alkaloids (n=11), flavonoids (n=23), terpenoids (n=7) and lignans (n=2). The most common inhibitory methods used to evaluate efficacy of these phytoconstituents included Gelatin Zymography, Western Blotting and real time polymerase chain reaction (RT-PCR) analysis. Moreover, current limitations, challenges and future directions of using such compounds have been critically discussed. This review underscores the potential implications of phytochemicals in the management of breast cancer which could lessen the growing encumbrance of disease.